Navigating the labyrinth of healthcare workers' mental health - Zhang, Hai-long; Zhang, Qin-yuan (Frontiers in Public Health, 2025)
The prevalence of mental health issues such as burnout, anxiety, and depression, and the negative impact on both healthcare workers and the healthcare system are notably high. Here, we introduced a dynamic model of mental health that includes stress, coping mechanisms, and resilience, and incorporates individual, organizational, and socio-cultural factors. It emphasized the importance of addressing moral dilemmas, high workloads, and systemic deficiencies that contributed to mental health risks. Additionally, innovative tools like AI-based predictive models were used to identify at-risk individuals early. In a word, special attention was called for comprehensive support systems, national policies, and cross-cultural research to improve healthcare workers' mental wellbeing. Ultimately, we stressed the need for systemic reforms and individualized interventions to safeguard the mental health of healthcare workers and ensure better patient care. This article highlighted the global mental health challenges faced by healthcare workers, especially in the context of the COVID-19 pandemic and other health crises.